A novel biodegradable film from edible mushroom (F. velutipes) by product: Microstructure, mechanical and barrier properties associated with the fiber morphology. (June 2018) - Wang, Wenhang; Zhang, Kai; Li, Cong; Cheng, Shan; Zhou, Jingyang; Wu, Zinan
Abstract: In order to efficiently utilize mushroom-processing waste discharge, insoluble fiber (FVIF) from aged Flammulina velutipes stipe was prepared with a series of wet milling steps of colloid mill (CM), PFI, low pressure homogenization (LPH) and high pressure homogenization (HPH) and formed into film by casting method. The SEM images depicted that morphology and size of FVIF varied (fibrous to spherical; 5 um to 50 nm) with a tendency of uniform and micronization as homogenization intensity increased. Accordingly, HPH-fiber film presented a smoother surface and more compact internal structure, especially a higher tensile strength (49.83 ± 3.63 MPa) and a better barrier property to water vapor (0.095 ± 0.003 a g·mm/m 2 ·h·kPa) and oxygen (9.96 ± 0.63 meq/kg). Moreover, HPH benefited the film's thermal stability, color and transparency. It confirmed that film performance is closely associated with fiber morphology and HPH provides a potential approach to develop new edible film from mushroom byproducts. Highlights: F . velutipes insoluble fibers (FVIF) were obtained by a series of grinding steps. FVIF morphology varied depending on preparation method. Film performance was governed by FVIF size and morphology. The FVIF film was available for biodegradable/edible packaging.